New Species of Limpets from the Neogene of Alaska (Patellogastropoda: Mollusca) - Lindberg, David R.; Marincovich, Louie (ARCTIC, 1988)
Two new species of patellogastropod limpets from the Miocene-Pliocene of Alaska are described - Patelloida gradatus new species from the Unga Conglomerate Member of the Bear Lake Formation at Cape Aliaksin, Alaska Peninsula, southwestern Alaska, and Niveotectura myrakeenae new species from the Yakataga Formation in the northeastern Gulf of Alaska. A third species from the Narrow Cape Formation of Kodiak Island may be referrable to Patelloida sookensis Clark and Arnold, 1923, a species previously known only from Vancouver Island, Canada. These and other species of Patelloidinae dominated the northeastern Pacific patellogastropod fauna for over 60 m/y. The presence in Alaska of these three warm-water limpet species may be related to the middle Miocene warm-water event that is well documented elsewhere in the North Pacific. However, regional cooling during the late Neogene drove this predominantly tropical group from higher latitudes, leaving them poorly represented in the Holocene boreal fauna.Key words: paleontology, historical biogeography, paleoecology, fossil gastropods, Miocene, Patellogastropoda, Patelloida, limpets Mots clés: paldontologie, biogéographie historique, paléoécologie, fossiles gastéropodes, miocène, patelles gastéropodes, Patelloida, patelles